2016
DOI: 10.1186/s12866-016-0795-3
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium glutamicum possesses β-N-acetylglucosaminidase

Abstract: BackgroundIn Gram-positive Corynebacterium glutamicum and other members of the suborder Corynebacterianeae, which includes mycobacteria, cell elongation and peptidoglycan biosynthesis is mainly due to polar growth. C. glutamicum lacks an uptake system for the peptidoglycan constituent N-acetylglucosamine (GlcNAc), but is able to catabolize GlcNAc-6-phosphate. Due to its importance in white biotechnology and in order to ensure more sustainable processes based on non-food renewables and to reduce feedstock costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Corynebacterium glutamicum , which has been engineered to utilize GlcN and GlcNAc ( Matano et al, 2014 , 2016 ), cannot utilize MurNAc since no growth was observed in minimal medium with 25 mM MurNAc and 25 ± 0.1 mM MurNAc remained in the growth medium after 25 h of incubation ( Figure 2A ). As expected, the C. glutamicum genome lacks genes encoding a MurNAc PTS and MurNAc-6-phosphate etherase for uptake and conversion of MurNAc to GlcNAc-6-phosphate, an endogenous intermediate of C. glutamicum metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Corynebacterium glutamicum , which has been engineered to utilize GlcN and GlcNAc ( Matano et al, 2014 , 2016 ), cannot utilize MurNAc since no growth was observed in minimal medium with 25 mM MurNAc and 25 ± 0.1 mM MurNAc remained in the growth medium after 25 h of incubation ( Figure 2A ). As expected, the C. glutamicum genome lacks genes encoding a MurNAc PTS and MurNAc-6-phosphate etherase for uptake and conversion of MurNAc to GlcNAc-6-phosphate, an endogenous intermediate of C. glutamicum metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The mutated variation of murP was called murP opt . The genes of murP, crr and murQ were amplified via PCR from genomic DNA of E. coli K-12, while nagE from C. glycinophilum , was amplified from pVWEx1_ nagE ( Matano et al, 2016 ). The primers used in this study (see Supplementary Table S1 ) were obtained from Metabion international AG, Planegg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. glutamicum has been engineered to produce amino acids from pure and technical grade glycerol (Rittmann et al, 2008 ; Meiswinkel et al, 2013b ). Access to nitrogenous sidestreams from the fishery industry such as glucosamine or N -acetyl-glucosamine is important if the target product is containing nitrogen atoms (Matano et al, 2014 , 2016 ). For products lacking nitrogen atoms, access to lignocellulosics is pivotal (Gopinath et al, 2011 ; Buschke et al, 2013 ; Meiswinkel et al, 2013a ; Hadiati et al, 2014 ; Matsuura et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Engineering microbes to utilize abundant polysaccharides from crustacean exoskeletons in order to produce chemicals has attracted extensive attention from researchers. Generally, the metabolic pathway of N-acetylglucosamine consists of a specific transport system and two enzyme actions, catalyzed by N-acetylglucosamine-6-phosphatedeacetylase (encoded by nagA) and glucosamine-6P deaminase (encoded by nagB), converting N-acetylglucosamine to fructose-6-phosphate that enters the glycolytic pathway (Matano et al, 2016). In C. glutamicum, the absence of a specific uptake system prevents the utilization of extracellular N-acetylglucosamine, requiring heterogeneous expression of nagE from Corynebacterium glycinophilum; this expression enables prompt transportation and feasible assimilation of N-acetylglucosamine.…”
Section: N-acetylglucosaminementioning
confidence: 99%